2022
DOI: 10.3389/fneur.2022.690048
|View full text |Cite
|
Sign up to set email alerts
|

Functional Network Changes After High-Frequency rTMS Over the Most Activated Speech-Related Area Combined With Speech Therapy in Chronic Stroke With Non-fluent Aphasia

Abstract: ObjectiveHigh-frequency repetitive transcranial magnetic stimulation (HF-rTMS) to the lesional hemisphere requires prudence in selecting the appropriate stimulation spot. Functional near-IR spectroscopy (fNIRS) can be used in both selecting the stimulation spot and assessing the changes of the brain network. This study aimed to evaluate the effect of HF-rTMS on the most activated spot identified with fNIRS and assess the changes of brain functional network in the patients with poststroke aphasia.MethodsA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Conversely, Hara et al (2017) applied HF-rTMS to the lesioned hemisphere, resulting in increased activity in the contralateral hemisphere. Recently, Chang et al's (2022) study confirmed that in poststroke stable aphasia patients, language function improves and cortical-cortical interactions change when HF-rTMS is used to target the most active language-related area identified in advance by functional near-infrared spectroscopy (fNIRS). This suggests that HF-rTMS may have promising therapeutic effects on chronic aphasia patients.…”
Section: Discussionmentioning
confidence: 81%
“…Conversely, Hara et al (2017) applied HF-rTMS to the lesioned hemisphere, resulting in increased activity in the contralateral hemisphere. Recently, Chang et al's (2022) study confirmed that in poststroke stable aphasia patients, language function improves and cortical-cortical interactions change when HF-rTMS is used to target the most active language-related area identified in advance by functional near-infrared spectroscopy (fNIRS). This suggests that HF-rTMS may have promising therapeutic effects on chronic aphasia patients.…”
Section: Discussionmentioning
confidence: 81%
“…Both HF-rTMS and LF-rTMS applied to one hemisphere, have demonstrated effectiveness in treating NFA ( 13 ). HF-rTMS enhances cerebral cortex excitability and revives bilateral cerebral hemisphere function by stimulating local neurons in the language center ( 98 ). However, HF-rTMS can cause intracranial hemorrhage and epilepsy, leading to its limited use in clinical and research settings.…”
Section: Discussionmentioning
confidence: 99%
“…In the domain of another non-invasive brain stimulation technique, repetitive TMS, a recent development involves the use of a navigation method by functional near-infrared spectroscopy (fNIRS) [11]. The fNIRSaided navigation method exhibits excellent sensitivity and topographical resolution compared with the conventional MEP-guided method [12].…”
Section: Discussionmentioning
confidence: 99%